2012
DOI: 10.1590/s0104-42302012000400021
|View full text |Cite
|
Sign up to set email alerts
|

Oscilação do humor em pacientes com doença de Crohn: incidência e fatores associados

Abstract: In this study, a high MS incidence (58%) was found in patients with CD. Female gender and absence of previous surgery from CD complications were associated with a higher MS incidence. Periodic psychological assessment could be useful to detect and approach MS in patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
0
8
0
9
Order By: Relevance
“…Concerning to the type of IBD, the majority of our participants presented Crohn's disease as a diagnosis. Studies have warned to the rapid increase of this disease in comparison to others IBDs (SOUZA et al, 2002;ZALTMAN, 2007;LIMA, 2012;MARANHÃO;VIEIRA;CAMPOS, 2015) The literature has mentioned that the rapid increase and prevalence of IBD in developing countries is due to the Western lifestyle linked to the environmental factor of the IBDs genesis (ZALTMAN, 2007). Besides, Shanahan, 2002, points out that in addition to family history and predisposing environmental factors, other factors such as antigens derived from the microbiota, degree of exposure to intestinal pathogens, smoking, and use of nonsteroidal anti-inflammatory drugs appear to be linked to the development of the IBDs (SHANAHAN, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning to the type of IBD, the majority of our participants presented Crohn's disease as a diagnosis. Studies have warned to the rapid increase of this disease in comparison to others IBDs (SOUZA et al, 2002;ZALTMAN, 2007;LIMA, 2012;MARANHÃO;VIEIRA;CAMPOS, 2015) The literature has mentioned that the rapid increase and prevalence of IBD in developing countries is due to the Western lifestyle linked to the environmental factor of the IBDs genesis (ZALTMAN, 2007). Besides, Shanahan, 2002, points out that in addition to family history and predisposing environmental factors, other factors such as antigens derived from the microbiota, degree of exposure to intestinal pathogens, smoking, and use of nonsteroidal anti-inflammatory drugs appear to be linked to the development of the IBDs (SHANAHAN, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The literature emphasizes that there are controversies about the development of anxiety and depression in patients with IBD (BARROS, 2016;FALCÃO;MARTINELLI, 2016;LIMA, 2012;(SERAFIM;COSTA, 2009;BOING, et al, 2012. Some researchers (FALCÃO;MARTINELLI, 2016;LIMA, 2012) have found no evidence of association between these comorbidities, while others (BARROS, 2016;(SERAFIM;COSTA, 2009;BOING, et al, 2012) have confirmed that depression and anxiety are common in patients with IBD, however, anxiety and depression are more prevalent in patients who experience exacerbations than in patients in remission (MITTERMAIER et al, 2004). Kurina et al found that both depression and anxiety are more present in Ulcerative Colitis than in Crohn's disease (KURINA et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as opções, a mais escolhida foi alteração de humor (Tabela 3). Lima et al 18 já haviam encontrado resultado semelhante ao estudar a oscilação do humor, presente na maioria dos pacientes (58%) com DC de um ambulatório de DII de Juiz de Fora. Outra modificação que se destacou entre os participantes foi a dificuldade financeira, que pode ter sido gerada pelas mudanças profissionais ocorridas, como a perda do emprego, a redução de horas trabalhadas ou a mudança de carreira (Tabela 3).…”
Section: Mudanças Psicossociaisunclassified
“…Dessa forma, aspectos emocionais poderiam agravar os sintomas ou provocar recidivas. Além disso, as DII comprometem a qualidade e a expectativa de vida dos pacientes e representam um impacto social e psicológico importante 8,9,15,18 .…”
Section: Introductionunclassified
See 1 more Smart Citation